Dynamics of hematological parameters in patients with HRTB/HIV with levels of CD4+lymphocytes 200-50 cells/μl in imunoglobulin therapy application - Matsehora, N. A.; Kaprosh, A. V. (Journal of Education, Health and Sport, 2019)
Introduction. According to the World Health Organization (WHO), in 2017 about 10 million people became ill with TB in the world. Also, WHO reports that Ukraine belongs to countries where the number of patients with chemo-resistant tuberculosis (HRTB) is one of the largest in the world. In 2017, TB caused 1.6 million deaths, of which 300,000 had a combined HIV/TB infection.The purpose and tasks of the study. To study the hematologic changes in patients co-infected HRTB / HIV at the level of CD4 + lymphocytes 200 - 50 cells/ml and evaluate the effectiveness of immunoglobulin therapy.Materials and methods. The study involved 52 patients with combined HRTB / HIV disease, aged 20 to 55 years. The study of hematological parameters was performed on the basis of the laboratory of the Odessa regional anti-tuberculosis dispensary, the calculation was performed on the automatic hematological analyzer Sysmex ХР-300 3-diff with direct counting of neutrophils (Japan).Results and discussion. In patients with HRTB / HIV with a level of CD4 + lymphocytes below 200 cells / μl, hematological parameters before the start of anti-TB therapy were characterized by the fact that patients of both groups were more likely to have leukocytosis than leukopenia, that is: 3.5 times more often in patients in group 1 (26.9% vs. 7.7%), and 9.1 times in the 2nd group (34.6% vs. 3.8%); lymphopenia - 2 times higher than lymphocytosis in group 1 and the same expressed in group 2 (see table). Monocytopenia was noted in 3.8%, monocytosis was registered 4 times more often in group 1, and in 1.5 times - in the 2nd. The frequency of eosinophilia reached 15.4% and 11.5%, in the first and second groups, respectively. Increases in neutrophils occurred in 30.8% and 38.5% of patients in groups 1 and 2, respectively.Lung anemia was registered more often in both groups than anemia of average grade - 2 times more often in the 1 st (46.2% vs. 23.1%), and the second group (53.8% vs. 26.9%) , and severe anemia was 3.8% in the 1st group and 7.7% in the second group of the subjects.Thrombocytopenia was diagnosed in 23.1% and 19.2% of patients in groups 1 and 2. Increasing the rate of erythrocyte sedimentation was determined in a greater number of patients - 69.2% of the examined group 1 and 65.4% of the 2nd group.Conclusions. After the use of intravenous IgG in the combination therapy of patients with HRTB/HIV, there was a significant reduction in the manifestations of inflammation and infectious activity compared with patients taking only anti-TB drugs and ARVT according to treatment standards.